Implementasi Customer Relationship Management (Crm) di Industri Kecil Menengah (Ikm) Furnitur Menggunakan Microsoft Excel dan Visual Basic For Application (VBA) - Yessi Nasia Ulfia; Fitri Indah Puspitaningsih; Fesa Putra Kristanto (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
Small and Medium Furniture Industry is one of the leading commodities of Kendal Regency and has important role in regional economy. Furniture IKM, which was only focused onproducts, must now change its strategy to focus on customers and implement modern management and be able to build relationships with customers. Consumers need more than just the value offered and have unique needs so companies need to think about creating marketing concepts that not only rely on the company's internal capabilities, but also involve consumer feelings. Maintaining good relation swith customers and increasing their loyalty through the development and fulfillment of customer needs is one of IKM furniture strategies in developing business. From the description, the author took the initiative to help design an information system based on Customer Relationship Management (CRM) as an industry 4.0 technology to digitize marketing, especially for managing customers. The implementation of CRM-based information systems starts from collecting data, then analyze business processes, and using case diagrams. The next step is to implement a CRM system using Microsoft Excel VBA. Finally analyze and evaluate CRM implementations in Furniture IKM. From this research we get a CRM system that is suitable for furniture IKM business processes.